The capacities of thin plated stiffened T-stubs. (November 2021) - Özkılıç, Yasin Onuralp
Abstract: The stiffeners, also known as ribs, have a great influence on the behavior of the extended end-plate connections. The end-plate connections can be idealized by making use of equivalent T-stubs. The effects of the stiffener on the behavior of T-stubs were experimentally investigated with an extensive set of parameters. Flange thickness, flange width, gage distance, distance from a T-stub stem to bolt row, vertical edge distance, bolt diameter and weld thickness are selected as the parameters. Pursuant to this goal, 44 stiffened T-stubs were tested under monotonic loading up to failure. The load-displacement curve of each T-stubs is presented and the results are evaluated with the predicted capacity by AISC 358 and EC3. The results revealed that the current provisions underestimate the capacity with high standard deviations. Therefore, a new design expression is proposed utilizing the yield line mechanism to estimate the plastic capacity more accurately. Moreover, an expression is developed to predict the ultimate capacity. Graphical abstract: Unlabelled Image Highlights: 44 experiments were conducted to investigate the capacity of thin-plated stiffened T-stubs. AISC 358 and EC 3 underestimate the capacity of stiffened T-stubs. A new yield line pattern is developed to predict the plastic capacity of stiffened T-stubs. An expression is proposed to estimate the ultimate capacity of stiffened T-stubs. The proposed modifications accurately predict the plastic and ultimate capacity of stiffened T-stubs.